Bilateral cervical ectopic thymic nodules with accessory thyroid tissue and an ectopic parathyroid in the neck region - Wea-Lung Lin; Chung-Hung Tsai; Chun-Lan Liu; Lien-Chuan Yang; Wan-Ru Chao (Elsevier, 2011)
Some remnants of thymic tissue may be deposited along the pathway of the descent of the neck during embryologic development of the thymus. Ectopic thymic tissue is usually deposited along the pathway from the mandibular angle to the manubrium of the sternum. Most reported cases of an ectopic thymus occurred in children, and cases are less common in adults. We report a 26-year-old woman, who was incidentally found to have 2 neck nodules on the posterior side of the bilateral upper pole of the thyroid gland while undergoing a subtotal thyroidectomy. The left-side neck nodule showed accessory thyroid follicles intermixed with ectopic thymic tissue, and the right-side neck nodule was ectopic parathyroid tissue together with ectopic thymic tissue.